PENGARUH RELIGIOSITAS, CITRA DESTINASI, PROMOSI, DAN FASILITAS RAMAH MUSLIM TERHADAP KEPUASAN BERKUNJUNG DESTINASI HALAL DI MALANG (Studi Kasus Pada Mahasiswa Aktif FEB Unisma Angkatan 2018) - Afda Maulidiyah; Afifudin Afifudin; Hariri Hariri (Fakultas Ekonomi dan Bisnis Universitas Islam Malang, 2022)
This study aims to determine the effect of Religiosity, Destination Image, Promotion, and Muslim Friendly Facilities on Satisfaction in Visiting Halal Destinations in Malang. This type of research is a quantitative survey research. In this study, the sample taken was active students of the Faculty of Economics and Business, Islamic University of Malang batch 2018 with a total of 135 people. This research uses quantitative data and methods the collection is by using a questionnaire via google form and measured by a Likert scale. The analytical tool used is multiple linear regression analysis using SPSS. The results of the study partially show that: 1) Religiosity has a positive and significant effect on visiting satisfaction. 2) Destination image has a significant positive effect on visiting satisfaction. 3) Promotion has no positive and significant effect on visiting satisfaction. 4) Muslim friendly facilities have a positive and significant effect on visiting satisfaction.